Facial topical cream promotes facemask tolerability and compliance during COVID-19 pandemic - Olumuyiwa A. Bamgbade, FRCPC; Renee N. Richards, MBBS; Martha Mwaba, MBChB; Rita N. Ajirenike, MBBS; Lidya M. Metekia, MD; Bolusefe T. Olatunji, MBBS (Journal of Taibah University Medical Sciences, 2022)
الملخص: أهداف البحث: يعتبر استخدام قناع الوجه ضروريا للعلاج اثناء جائحة كوفيد -۱٩. قد تسبب اقنعة الوجه اعتلال جلدي بالوجه. قد تقلل الكريمات الموضعية من مضاعفات اقنعة الوجه. تبحث هذه الدراسة السريرية تأثير الكريمات الموضعية المختلفة على تحمل قناع الوجه ومضاعفاته. طرق البحث: أجريت هذه الدراسة المستقبلية المبنية على المشاهدة على ٨٠ بالغا. اختار المشاركون طواعية استخدام الكريمات الموضعية أثناء استخدام قناع الوجه. تم جمع البيانات باستخدام مقاييس تم التحقق من صحتها قبل وبعد وضع الكريم الموضعي. النتائج: استخدم ٢۳٫٨٪ من المشاركين جل ليدوكاين، استخدم ۱٧٫٥٪ الفازلين، استخدم ۱٦٫٢٪ كريم الهيدروكورتيزون، استخدم ۱٦٫٢٪ كريم دايفين هيدرامين، استخدم ۱۳٫٨٪ كريم أرنيكا، واستخدم ۱٢٫٥٪كريم أوكسيد الزنك. كانت مدة استخدام قناع الوجه ٦ ساعات بين الموظفين و٤ ساعات بين المرضى. كانت مدة استخدام قناع الوجه مماثلة مع الكريم الموضعي وبدونه. كان ارتفاع درجة حرارة الوجه أقل مع جميع الكريمات. كان احمرار الوجه أقل مع جميع الكريمات. كان ألم الوجه أقل لجميع الكريمات. كان التوافق مع قناع الوجه أفضل مع جميع الكريمات. كان ارتفاع درجة حرارة الوجه الأقل مع ليدوكاين الموضعي. كان احمرار الوجه المبكر الأقل مع الهيدروكورتيزون الموضعي أو دايفين هيدرامين. كان الاحمرار الشديد الأقل مع الهيدروكورتيزون الموضعي أو أوكسيد الزنك. كان ألم قناع الوجه الأقل مع ليدوكاين الموضعي. كان التوافق مع قناع الوجه الأفضل مع ليدوكاين الموضعي. حصل الفازلين على أفضل رضا ورائحة من قبل المستخدمين. الاستنتاجات: تقلل الكريمات الموضعية مضاعفات قناع الوجه، وذلك بتعزيز توافق قناع الوجه. يعتبر الليدوكاين الموضعي الأكثر فعالية في تقليل الألم وتمكين التوافق لقناع الوجه. تعتبر الكريمات الموضعية الهيدروكورتيزون ودايفين هيدرامين وأكسيد الزنك فعالة لتقليل احمرار الوجه. حصل الفازلين الموضعي على أفضل رضا من المستخدمين. Abstract: Objectives: Facemask use is essential for managing the COVID-19 pandemic, but may cause facial dermopathy. Topical creams may minimise facemask complications. This clinical study explores the impact of different topical creams on facemask tolerability and complications. Methods: This was a prospective observational study involving 80 adults. Participants voluntarily chose and used topical creams during facemask use. Data were collected using validated scales before and after topical cream application. Results: About 23.8% of the participants used lidocaine gel, 17.5% used petrolatum, 16.2% used hydrocortisone cream, 16.2% used diphenhydramine cream, 13.8% used arnica cream, and 12.5% used zinc oxide cream. Duration of facemask use was 6 h amongst staff and 4 h amongst patients, and was similar both with and without topical cream. Facial temperature rise was lower with all creams (p = 0.033), as was facial redness (p = 0.037) and facial pain (p = 0.025). Facemask compliance was better for all creams (p = 0.015). The facial temperature rise was the lowest with topical lidocaine (p = 0.021). Early facial redness was lowest with topical hydrocortisone or diphenhydramine (p = 0.042). Severe redness was lowest with topical hydrocortisone or zinc oxide (p = 0.044). Facemask pain was lowest with topical lidocaine (p = 0.035), and facemask compliance was best with topical lidocaine (p = 0.001). Petrolatum had the best user satisfaction and odour ratings (p = 0.041). Conclusion: Topical creams minimise facemask complications, thereby promoting compliance; topical lidocaine was the most effective in reducing pain and enabling facemask compliance. Topical hydrocortisone, diphenhydramine, and zinc oxide were effective in reducing facial redness, and topical petrolatum produced the best user satisfaction.